What Information Do Clinicians Deem Important for Counseling Parents Facing Extremely Early Deliveries?: Results from an Online Survey - Kim, Brennan Hodgson; Feltman, Dalia M.; Schneider, Simone; Herron, Constance; Montes, Andres; Anani, Uchenna E.; Murray, Peter D.; Arnolds, Marin; Krick, Jeanne (American Journal of Perinatology, 2021)
Objective The study aimed to better understand how neonatology and maternal fetal medicine (MFM) physicians convey information during antenatal counseling that requires facilitating shared decision-making with parents facing options of resuscitation versus comfort care after extremely early deliveryStudy Design Attending physicians at US centers with both Neo and MFM fellowships were invited to answer an original online survey about antenatal counseling for extremely early newborns. The survey assessed information conveyed, processes for facilitating shared decision-making (reported separately), and clinical experiences. Neonatology and MFM responses were compared. Multivariable logistic regression analyzed topics often and seldom discussed by specialty groups with respect to respondents' clinical experience and resuscitation option preferences at different gestational weeks.Results In total, 74 MFM and 167 neonatologists representing 94% of the 81 centers surveyed responded. Grouped by specialty, respondents were similar in counseling experience and distribution of allowing choices between resuscitation and no resuscitation for delivery at specific weeks of gestational ages. MFM versus neonatology reported similar rates of discussing long-term health and developmental concerns and differed in all other categories of topics. Neonatologists were less likely than MFM to discuss caregiver impacts (odds ratio [OR]: 0.14, 95% confidence interval [CI]: 0.11–0.18, p < 0.001) and comfort care details (OR: 0.19, 95% CI: 0.15–0.25, p < 0.001). Conversely, neonatology versus MFM respondents more frequently reported “usually” discussing topics pertaining to parenting in the NICU (OR: 1.5, 95% CI: 1.2–1.8, p < 0.001) and those regarding stabilizing interventions in the delivery room (OR: 1.8, 95% CI: 1.4–2.2, p < 0.001). Compared with less-experienced respondents, those with 17 years' or more of clinical experience had greater likelihood in both specialties to say they “usually” discussed otherwise infrequently reported topics pertaining to caregiver impacts.Conclusion Parents require information to make difficult decisions for their extremely early newborns. Our findings endorse the value of co-consultation by MFM and neonatology clinicians and of trainee education on antenatal consultation education to support these families.Key Points
Keywords: periviable; antenatal counseling; decision-making; extreme prematurity; neonatal resuscitation; ethics; maternal fetal medicine; neonatology; physician attitudes